Behavior of Glass Fiber Reinforced Polymer Concrete Panels - Hussain, Hussain Fadhil; Al-Zuhairi, Alaa Hussein; Al-Mamory, Zainab Kareem; Al-Ahmed, Ali Hussein Ali (Engineering, Technology & Applied Science Research, 2025)
Glass Fiber Reinforced Polymer (GFRP) bars have gained popularity as a corrosion-resistant alternative to traditional steel reinforcement in Reinforced Concrete (RC) elements. This study investigates the flexural behavior of PRC panels reinforced with GFRP bars. The study variables included the GFRP reinforcement ratio and the number of embedded steel section distributions. Six concrete panels were fabricated, each measuring 2500 mm in length, with a rectangular cross-section of 750 mm in width and 150 mm in thickness. All panels were reinforced with GFRP bars and divided into two groups based on the reinforcement ratios of 0.532% and 0.266%. For each group, one panel served as the control specimen, while the remaining two were internally strengthened with embedded steel box sections, one with 2 steel sections and the other with 4 sections. The parametric study highlighted the effects of the reinforcement ratio and the inclusion of internal I-section steel shapes on the flexural performance of the panels. Compared to non-strengthened control slabs, the addition of steel elements significantly improved the structural performance, as evidenced by reductions in deflection, strains, and crack widths, as well as an increase in the ultimate load capacity and flexural stiffness at the ultimate loading stage. These findings underscore the effectiveness of combining GFRP reinforcement with embedded steel shapes to enhance the structural performance of PRC panel slabs.